Spain : memorandum of interview / Walter Citrine....Ebby Edwards - Edwards, Ebby; Citrine, Walter, 1887-1983
016b-0040-001 PRIVATE & CONFIDENTIAL. MEMORANDUM OF INTERVIEW. Date 18th October, 1937. Time 11 am to Reference WMC/FP/66 Presenter Sir W. Citrine. Mr. E. Edwards. SUBJECT. SPAIN. Mr. Ebby Edwards called at 11 a.m. this morning for the purpose of discussing the question of the proposed Commission or Delegation to Gijon. He stated that Mr. del Vayo had proposed a Commission of miners. The Executive of the Mineworkers' Federation had considered this matter, and whilst they were ready to take part in a Commission, it was felt that the matter should be dealt with on a wider basis. Mr. Edwards suggested that perhaps the National Council of Labour could deal with the matter at its next meeting. I recounted to Mr. Edwards my conversation with Mr. del Vayo and that I had suggested the Delegation being widened by the inclusion of one or two public men. I had also suggested that he should see Mr. Schevenels at Paris, to see whether the Delegation should take the international character which Mr. del Vayo desired. I informed Mr. Edwards that by appointment the Spanish Ambassador M. Ascarate [ Azcarate ], would be calling the following day, Tuesday 19th October, as I assumed he would have something to report in connection with the proposal. We decided to leave matters over until this interview had taken place. In the meantime I promised I would ascertain the manner in which a Commission could reach Gijon which was known to be cut off from communication by sea. I gave instructions that communication should be established by telephone with Mr. Schevenels, and he should be asked as to what was being done by the I.F.T.U. 292/946/16b/44